Analisis Implementasi Kebijakan Pemberdayaan Komunitas Adat Terpencil di Kabupaten Buru Provinsi Maluku - Maryam Trenggano; Khasan Effendy; Irwan Tahir; Sampara Lukman (Institut Pemerintahan Dalam Negeri (IPDN), 2020)
This research analyzed the implementation processing of Remote Indigenous Communities Empowernment in Buru District by using variable of Van Horn, They are; 1) The policy standarts and objectives; 2) resources ; 3) the communication Among organizations; 4) the characteristic of the implementing agency; 5) sosial, economic and political conditions, 6) implementor disposition. Furthermore, the researcher identified factors that become strength and weakness in the implementation. After that, formulate strategies and models that can applied in the implementation of empowernment. This research used qualitative design with analysis descriptive approach. Informants are determined by purposive sampling. Data collection was carried out by observation, interview, and documentatiom methods. Furthermore, data analysis ia carried out by steps: data reduction, presenting data, drawing conclusions and analyzing new models. The result showed that the implementation of sosial Empowernment to the residents of Remote Indigenous Communities in Wanfudinar Village, Buru District went well, it can be seen in some indicators such as There were semi permanent houses for residents, and the other publik facilities. Ini addition, the implementation Empowernment was also seen through behavior changes of residents who increasingly received change, awareness of embracing religion. Based on the results, the researcher formulate a strategy implementation of Remote Indigenous Communities Empowernment with ASOCA analysis method, and Formulate MARYAM model. (Manage, Acceptable, Review, Yield, Accountability, Measurable) that supports three requirement in the design namely understanding ,commitment, and synergy.